Modeling and Simulation of Point to Area Prediction on Digital Tv, Extensible to Other Technologies and Its Validation with Actual Field Records [Modelamiento y Simulación de Predicción Punto a Zona en Televisión Digital, Extensibles a Otras Tecnologías y Su Validación Con Mediciones Reales] - Kaschel-Carcamo, H (Institute of Electrical and Electronics Engineers Inc., 2016)
On this paper, worldwide Digital TV Standards (TDT) are reviewed as well as the approach and needs for point to area propagation modeling currently used worldwide to predict TDT broadcasting coverage. One of the models currently used for coverage calculations, the deterministic ITM (Irregular Terrain Model - Longley-Rice) based on Technical Note 101 Vol-I and II, as well as the empirical ITU-R-P1546-5 Model will be studied and analyzed. The modeling of TVD coverage of existing TVD stations will be performed with both Models and compared with actual coverage of exiting field strength surveys, performed by broadcast operators under the ITU recommendations specs. Finally, conclusions will be drawn on the pros and cons of each Model. © 2016 IEEE.